Effect of unstable aluminium chemistry on Arctic char ( Salvelinus alpinus ) - Poléo, Antonio BS; Bjerkely, Frode (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
Arctic char (Salvelinus alpinus) were exposed to a non-steady-state Al-rich medium (pH 5.8, total Al 480 µg·L -1 , total organic C 3.0 mg C·L -1 , Ca 2+ 2.9 mg·L -1 , temperature 7.5°C). An Al-poor medium (pH 5.2 and 5.8, total Al 99 µg·L -1 , total organic C 3.0 mg C·L -1 , Ca 2+ 2.9 mg·L -1 , temperature 8.0°C) acted as control. The Al-rich medium was acutely toxic to the Arctic char. Total mortality (percent) and mortality rate (LT 50 ) were highest in fish exposed to the Al-rich medium immediately after mixing and decreased systematically with water residence time (e.g., from 65 h at 1 min to 124 h at 3 min to more than 400 h at 15 min). Gill morphology changes, Al gill deposition, and haematological parameters revealed significant effects of Al, which all correlated with water residence time. Signs of acclimation or high difference in Al tolerance between individuals were observed. This indicates that effects of Al in fish are dependent on the degree of Al polymerisation and supports earlier indications that Arctic char are relatively tolerant of acidic Al-rich water.